Modelization of Blood-Borne Hypercoagulability in Myeloma: A Tissue-Factor-Bearing Microparticle-Driven Process - Papageorgiou, Loula; Alhaj Hussen, Kutaiba; Thouroude, Sandrine; Mbemba, Elisabeth; Cost, Héléne; Garderet, Laurent; Elalamy, Ismail; Larsen, Annette; Van Dreden, Patrick; Dimopoulos, Meletios A.; Mohty, Mohamad; Gerotziafas, Grigoris T. (TH Open, 2019)
Introduction Hypercoagulability is a common blood alteration in newly diagnosed chemotherapy naïve patients with multiple myeloma. The identification of the procoagulant potential of cancer cells, which is principally related to tissue factor (TF) expression, attracts particular interest. The mechanisms by which myeloma plasma cells (MPCs) activate blood coagulation have been poorly investigated.Aim To identify the principal actors related with MPCs that boost thrombin generation (TG).Methods TF and annexin V expression by MPCs and MPC-derived microparticles (MPC-dMPs) was analyzed by flow cytometry. TF activity (TFa) and TF gene expression were also determined. TG in the presence of MPCs or MPC-dMPs was assessed with the calibrated automated thrombogram assay (CAT) in normal human PPP and in plasma depleted of factor VII or XII. TG was also assessed in plasma spiked with MPCs and MPC-dMPs.Results MPC-dMPs expressed approximately twofold higher levels of TF as compared with MPCs. The TFa expressed by MPC-dMPs was significantly higher compared with that expressed by MPCs. MPCs and MPC-dMPs enhanced TG of human plasma. TG was significantly higher with MPC-dMPs compared with MPCs.Conclusion MPCs indirectly induce blood-borne hypercoagulability through the release of MPC-dMPs rich in TF. Since MPCs, expressing low TFa, represent a weak procoagulant stimulus, the hypercoagulability at the microenvironment could be the resultant of MPC-dMPs rich in TF.
Keywords: multiple myeloma; thrombin generation; tissue factor; microparticles; hypercoagulability